PENGARUH PEMANFAATAN LIMBAH CAIR PABRIK KELAPA SAWIT TERHADAP SIFAT KIMIA DAN FISIKA TANAH PADA LAHAN PERKEBUNAN KELAPA SAWIT MILIK PT.PMP KABUPATEN MAYBRAT - Aprilia Regita Sari; Markus Heryanto Langsa; Alfhons Daniel Sirampun (Jurnal Natural, 2019)
Palm oil mill effluent (POME) is the most abundant waste produced from palm oil mills. POME waste products from palm oil mills can pollute the surrounding environment. The main objective of this study was to determine the use of POME on soil fertility and increase the growth of oil palm plants and minimize negative impacts on the environment. The results of the research obtained are a combination of primary data (results of analysis carried out in oil palm plantations owned by PT PMP, Maybrat Regency before the POME application) and secondary data (results of analysis carried out at Angsana Estate oil palm plantations, South Kalimantan after POME application). The results obtained indicate that generally after the application of POME to the land will increase the value of the bulk density and decrease the value of soil porosity and soil permeability. There was a decrease in the percentage of soil porosity in the application area (LA, 28.75% and Flatbed, 23.47%) compared to without application (LK, 36.83%) in the soil depth up to 30 cm. On soils with a deeper depth (30-60 cm) the percent of land subsidence is almost the same as at a depth of 30 cm. Conversely, the addition of POME in the land application (LA) had an impact on the increase in bulk density (1.81 g / cm3) and soil permeability (4.16 cm / hour) compared without POME (LK) (1.48 g / cm3 and 4.08 cm / hour) for soil samples to a depth of 30 cm. The POME application increases the availability of organic matter (C-organic and nitrogen) in the surface soils. The highest P-available values ​​are seen at a depth of 0-20 cm and 20-40 cm in the flatbed. Also, POME on oil palm land tends to increase nutrient content in oil palm leaves compared to control land (without POME).